2008
DOI: 10.1016/j.str.2007.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Full-Length β-Catenin

Abstract: beta-catenin plays essential roles in cell adhesion and Wnt signaling, while deregulation of beta-catenin is associated with multiple diseases including cancers. Here, we report the crystal structures of full-length zebrafish beta-catenin and a human beta-catenin fragment that contains both the armadillo repeat and the C-terminal domains. Our structures reveal that the N-terminal region of the C-terminal domain, a key component of the C-terminal transactivation domain, forms a long alpha helix that packs on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
155
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(172 citation statements)
references
References 53 publications
7
155
1
2
Order By: Relevance
“…It has been previously speculated that low affinity charge interactions between the basic arm repeat domain and acidic terminal regions may effectively shield the arm repeats from nonspecific interactions (29). Consistent with this model, ␤-catenin lacking its entire CTD was found to coimmunoprecipitate numerous 32 P radioactively labeled species (supplemental Fig.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…It has been previously speculated that low affinity charge interactions between the basic arm repeat domain and acidic terminal regions may effectively shield the arm repeats from nonspecific interactions (29). Consistent with this model, ␤-catenin lacking its entire CTD was found to coimmunoprecipitate numerous 32 P radioactively labeled species (supplemental Fig.…”
Section: Discussionsupporting
confidence: 65%
“…With similar methods, two studies found that the CTD of ␤-catenin could compete its binding to the cadherin (39,47), but not TCF (47), raising the possibility that in a full-length protein the CTD may fold back along the arm domain in a closed conformation that restricts binding to some partners (27,47). However, specific binding between the CTD and the arm domain was not supported when Coomassie-stained gels were employed to quantify binding (19) or NMR spectroscopy was used to detect transient weak interactions (29). As these experi- ments are done in trans, it has remained untested whether a CTD tethered in cis could interact more effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HQ234356) has diagnostic protein domains and residues indicative of the ability to interact with classical cadherins. Oc_bcat contains at least 11 of the 12 conserved armadillo (arm) repeats (36,37) that are typical of eumetazoan β-catenin proteins (Fig. 3C) and shows 66.4% amino acid sequence identity with human β-catenin over the conserved arm-repeat region.…”
Section: Resultsmentioning
confidence: 99%
“…5 Structurally, b-catenin contains a series of 12 armadillo repeats, each of which is approximately 40 amino acids, surrounded by unstructured N-and C-terminal domains. 6 Protein-protein interaction mapping experiments have demonstrated that all 3 b-catenin domains are involved in both signaling and cytoskeletal interaction. 7,8 Over 38 b-catenin interaction partners have been documented (http://www.stanford.edu/group/nusselab/cgi-bin/ wnt/protein_interactions).…”
Section: Introductionmentioning
confidence: 99%